Research trends on clinical fecal microbiota transplantation: A biliometric analysis from 2001 to 2021 - Li, Yu; Ouyang, Yaobin; He, Cong (Frontiers in Immunology, 2022)
Background Numerous studies on fecal microbiota transplantation (FMT) have been conducted in the past two decades. We aimed to assess the research trends and hotspots in the field of FMT through a quantitative method. Materials and Methods The clinical studies of FMT published from 2001 to 2021 were extracted from the Web of Science database. We analyzed the countries, institutions, authors, and keywords of these articles and visually illustrated using VOSviewer and CiteSpace software. The current application of FMT in clinical practice, including indications, efficacy, adverse events, as well as its methodology, such as donor, delivery route, were also evaluated. Results A total of 227 records were finally identified. The number and rate of annual publications increased gradually. The USA ranked highest in the number of publications. Harvard University was the most influential institution, and Digestive Diseases and Sciences was the most productive journal. Kassam Zain published the most papers, and the high-frequency keywords were mainly related to diseases and techniques. Healthy donors were the most widely used donors, and frozen stool had the highest frequency of use. The predominant delivery route was endoscopy followed by oral capsules and enema. FMT was most frequently performed for the treatment of recurrent Clostridium Difficile Infection. The overall efficacy of FMT was 76.88%, and the incidence of minor and severe adverse events were 11.63% and 1.59%, respectively. Conclusions This study delineated a comprehensive landscape of the advancement in FMT field. Although in its infancy, FMT is a burgeoning option for the treatment of a variety of diseases associated with gut dysbiosis. To improve the efficacy and reduce adverse events, future studies are warranted to optimize the methodology of FMT.